Poučevanje strokovno-znanstvenega jezika na slovenskih univerzah - Logar, Nataša (Slovenščina 2.0, 2017)
In the article, we first give an overview of lists of readings that are compulsory and additional in the syllabuses of courses, where students of Slovenian universities learn about academic writing. To those we then add other Slovenian handbooks on this topic and review their contents. We also analyze and comment upon 52 guidelines for writing and editing diplomas and master's theses, collected from the web pages of all public Slovenian faculties. We highlight exemplary cases and point out issues that need further improvement.
Keywords: Slovene; Slovenian language; slovenščina; strokovno-znanstveni jezik; academic language; study readings; pogovorni jezik; študijska literatura; diploma and master's theses; guidelines for writing diplomas and master's theses; zaključna dela; navodila za pisanje diplomskih del